Dry groundwater wells in the western United States. (28th September 2017) - Perrone, D; Jasechko, S
Abstract: Declining groundwater levels are common in parts of the western US, but their impact on the ability of wells to pump groundwater is not known. Here we collate groundwater well records for the western United States and present the recorded locations, depths, and purposes of more than two million groundwater wells constructed between 1950 and 2015. We then use the well records to estimate the percentage of wells that were dry during the years 2013–2015. During the two year period, dry wells were concentrated in rural areas with high agricultural productivity, such as parts of the California Central Valley and the High Plains. Our results support anecdotal evidence that wells used for domestic purposes are more susceptible to drying than wells used for agricultural purposes throughout California's Central Valley because the former tend to be shallower. However, this is not the case in all regions. Our findings suggest that declining groundwater levels are threatening drinking water reliability and agricultural productivity, and consequently, have key implications for both domestic and agricultural water security. Ongoing reductions to groundwater storage are drying groundwater wells in the western US, and this manifestation of water scarcity warrants innovative groundwater management transcending status quos.